Implementation of e-Reports as a Means of Complaints for the Society - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Rodianto Rodianto; Chalvin Bebby Febrianto (STMIK Budi Darma, 2022)
Marga Karya Village is one of the villages located in Moyo Hulu District, Sumbawa Regency. The problem in Marga Karya Village is that in serving society complaints it is still manual and not computerized, where people come directly to the village office during working hours. This makes the process of service and delivery of information slow because it is limited by space and time. In fact, several village problems require a quick response and handling. In addition, data collection on public complaints is still recorded in a ledger which is carried out repeatedly. Based on these village problems, an e-report is needed as a means of reporting public complaints and making it easier for village office staff to record and process complaints as well as a means of conveying information regarding complaints that have been executed by the village. The e-report for Marga Karya Village was built using the prototype development method, and the system design used the Unified Modeling Language (UML). E-Lapor consists of 2 (two) user groups, namely the society and village officials. Residents will be able to access features in the form of Village Profiles, Reports, Report Status, Gallery, Contacts and Login. Meanwhile, village officials will be able to access the Complaints feature, Manage Complaints, Complaint Reports and User Data. . With e-Report, it facilitates communication between residents and the village in the service of complaining about the condition of village facilities without time and space limits